2021
DOI: 10.3390/ma14041028
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Temperature and Refractive Index Using High Temperature Resistant Pure Quartz Grating Based on Femtosecond Laser and HF Etching

Abstract: The optical fiber temperature and refractive index sensor combined with the hollow needle structure for medical treatment can promote the standardization of traditional acupuncture techniques and improve the accuracy of body fluid analysis. A double-parameter sensor based on fiber Bragg grating (FBG) is developed in this paper. The sensor materials are selected through X-ray diffraction (XRD) analysis, and the sensor sensing principle is theoretically analyzed and simulated. Through femtosecond laser writing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Thus, it is quite natural that the electrical and optical properties of these nodes are very different from the nearby areas. Indeed, this has been confirmed experimentally [37][38][39][40][41][42][43] (see also references therein). In particular, it has been shown that acupuncture points have higher electric conductivity, increased conductance and capacitance, reduced impedance, and elevated electrical potential compared to adjacent non-acupuncture points.…”
Section: Cyclotron Vs Acupuncturementioning
confidence: 56%
See 1 more Smart Citation
“…Thus, it is quite natural that the electrical and optical properties of these nodes are very different from the nearby areas. Indeed, this has been confirmed experimentally [37][38][39][40][41][42][43] (see also references therein). In particular, it has been shown that acupuncture points have higher electric conductivity, increased conductance and capacitance, reduced impedance, and elevated electrical potential compared to adjacent non-acupuncture points.…”
Section: Cyclotron Vs Acupuncturementioning
confidence: 56%
“…In particular, it has been shown that acupuncture points have higher electric conductivity, increased conductance and capacitance, reduced impedance, and elevated electrical potential compared to adjacent non-acupuncture points. For instance, the refractive index in the acupuncture points varies from 1.36 to 1.40: in the range 1.41 to 1.49 in epidermal tissues and 1.36 to 1.41 in dermal tissues over the wavelength range [42,44]. This can be compared with the refractive index 1.373 (1.380 and 1.401) of the human cornea and 1.386-1.406 of the human lens [45], which are significantly higher than the refractive index of 1.33 for bulk water.…”
Section: Cyclotron Vs Acupuncturementioning
confidence: 99%
“…This is especially suitable for distributed measurement. In recent years, researchers have carried out extensive research on temperature measurement with FBG sensor arrays [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that the pressure sensitivity of the sensor is 3.402 pm/kPa, in the range of 0-200 kPa, and the temperature response sensitivity is 19.29 pm/ • C at 20-55 • C; this structure is suitable for low pressure measurement. In the existing papers, the research mostly focuses on the low-pressure and low-temperature section; however, the single-parameter measurement of temperature can already reach a high temperature [45]. However, for the temperature measurement under high pressure, the current research generally stays at room temperature, and there is less measurement and monitoring in the high-temperature and high-pressure complex environments.…”
Section: Introductionmentioning
confidence: 99%